Low Dose CT Denoising by ResNet With Fused Attention Modules and Integrated Loss Functions - Marcos, Luella; Alirezaie, Javad; Babyn, Paul (Frontiers in Signal Processing, 2022)
X-ray Computed Tomography (CT) is a non-invasive medical diagnostic tool that has raised public concerns due to the associated health risks of radiation dose to patients. Reducing the radiation dose leads to noise artifacts, making the low-dose CT images unreliable for diagnosis. Hence, low-dose CT (LDCT) image reconstruction techniques has offered a new challenge in the research area. In this study, a deep neural network is proposed specifically a residual network (ResNet) using dilated convolution, batch normalization and rectified linear unit (ReLU) layers with fused spatial- and channel- attention modules to enhance the quality of LDCT images. The network is optimized using the integration of per-pixel loss, perceptual loss via VGG16-net and dissimilarity index loss. Through an ablation experiment, these functions show that they could effectively prevent the edge-over smoothing, improve image texture and preserve the structural details, respectively. Finally, comparative experiments showed that the qualitative and quantitative results of the proposed network outperform state-of-the-art denoising models such as block-matching 3D filtering (BM3D), Markovian-based patch generative adversarial network (patch-GAN), and dilated residual network with edge detection (DRL-E-MP).